EFFECT OF DATURA METEL ON CROP GROWTH AND PHYSIOLOGY OF BELL PEPPER - A. Javaid; N. Jabeen; I. H. Khan; A. Shoaib (Journal of Animal and Plant Sciences, 2021)
Generally, crop residue is mixed in the soil to improve soil fertility that leads to enhanced crop growth and yield. However, in the present study, instead of the use of conventional crop residues, the effect of soil amendment with dry biomass of a weed Datura metel L. was studied on growth, yield and physiology of green bell pepper (Capsicum annuum L.). Different concentrations of dry biomass of D. metel (DBD) viz. 0.5, 1, 1.5, 2, 2.5 and 3% were mixed in the potting soil, left for one week after irrigation, and bell pepper seedlings were transplanted. In general, there was a gradual increase in different parameters of vegetative and reproductive growth of bell pepper due to an increase in the concentration of DBD up to 2% and a decline thereafter. A maximum increase of 44%, 45%, 14%, 38% and 83% in shoot length, shoot dry weight, root dry weight, and the number and dry weight of fruits, respectively, were observed due to application of DBD as compared to control. A 3% DBD application drastically reduced the plant growth and yield as compared to control or lower doses of DBD. Chlorophyll content was significantly increased by 1% DBD. Phenolic content was decreased by increasing DBD concentration and the effect of 2.5% amendment was significant (P≤0.05). Soil amendment had an insignificant effect on protein content and activities of peroxidase (POX) and phenylalanine ammonia lyase (PAL). Polyphenol oxidase (PPO) activity was significantly enhanced by 2.5 and 3% DBD. This study concludes that a 2% soil amendment with DBD can significantly improve growth and yield of bell pepper.
Keywords: Bell pepper; Datura metel; plant physiology; soil amendment